2018
DOI: 10.1002/cbic.201800471
|View full text |Cite
|
Sign up to set email alerts
|

Masking the Peroxidase‐Like Activity of the Molybdenum Disulfide Nanozyme Enables Label‐Free Lipase Detection

Abstract: Two-dimensional MoS nanoparticles (2D-nps) exhibit artificial enzyme properties that can be regulated at bio-nanointerfaces. We discovered that protein lipase is able to tune the peroxidase-like activity of MoS 2D-nps, offering low-nanomolar, label-free detection and identification in samples with unknown identity. The inhibition of the peroxidase-like activity of the MoS 2D-nps was demonstrated to be concentration dependent, and as low as 5 nm lipase was detected with this approach. The results were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Regulation of nanozyme activity with chemical or biological modifications is an ongoing effort for improving the enzymatic reaction. Derivatization of nanozymes or the reaction environment with oligonucleotides, [22,23] ions, [24] proteins, [16] other nanoparticles [25] can regulate the enzymatic activity constructively or destructively. We have observed interference of metal ions with the peroxidase activity of 2D nanozymes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulation of nanozyme activity with chemical or biological modifications is an ongoing effort for improving the enzymatic reaction. Derivatization of nanozymes or the reaction environment with oligonucleotides, [22,23] ions, [24] proteins, [16] other nanoparticles [25] can regulate the enzymatic activity constructively or destructively. We have observed interference of metal ions with the peroxidase activity of 2D nanozymes.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to many natural enzymes, nanozymes can be vulnerable to composition of a reaction medium [16,17] . Metal ions are often unavoidable part of a sample matrix and their effects on the enzyme‐catalyzed reactions have been documented [18,19] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Mo-based nanozymes can be used to detect reductive small biomolecules such as GSH, Cys, vitamin B1, and lipase, which can inhibit the enzyme-like activity of nanozymes in the presence of dual substrates such as TMB and H 2 O 2 (Figure 8C). 79,94,108,109 By monitoring the degree of color fading of organic substrates, these reductive small biomolecules can be quantitatively detected.…”
Section: 1mentioning
confidence: 99%
“…This novel material acted as a tri-enzymatic mimic with catalase, peroxidase and oxidase activity ( Figure 7). Later, Nandu et al showed that out of many proteins, lipase selectively masked the peroxidase activity of 2D MoS 2 [39], as indicated by the increasing K m values, i.e., decreasing affinity towards H 2 O 2 . The v max value was also decreased by more than 94% in the presence of lipase.…”
Section: Chalcogenide Structuresmentioning
confidence: 99%
“…In addition, 2D materials possess unusual electronic, mechanical and optical properties and hence, they can be used as building blocks in a wide range of composites. Concerning the contemporary applications of 2D compounds, they serve as efficient catalysts for water splitting [6][7][8][9][10][11][12][13][14][15] or organic reactions [16][17][18][19][20][21], drug carriers [22][23][24][25][26][27][28][29][30][31], sensors [32][33][34][35][36][37][38][39], materials for energy production and storage [2,15,21,[40][41][42][43][44][45][46][47][48][49] or adsorbers [50]…”
Section: Introductionmentioning
confidence: 99%